Recent progress of electrode architecture for MXene/MoS2 supercapacitor: preparation methods and characterizations - Mohd Abid, Mohd Asyadi Azam; Kosnan, Muhammad Akmal; Safie, Nur Ezyanie; Munawar, Rose Farahiyan; Takasaki, Akito (MDPI, 2022)
Since their discovery, MXenes have conferred various intriguing features because of their distinctive structures. Focus has been placed on using MXenes in electrochemical energy storage including a supercapacitor showing significant and promising development. However, like other 2D materials, MXene layers unavoidably experience stacking agglomeration because of its great van der Waals forces, which causes a significant loss of electrochemically active sites. With the help of MoS2, a better MXene-based electrodecan is planned to fabricate supercapacitors with the remarkable electrochemical performance. The synthesis of MXene/MoS2 and the ground effects of supercapacitors are currently being analysed by many researchers internationally. The performance of commercial supercapacitors might be improved via electrode architecture. This analysis will support the design of MXene and MoS2 hybrid electrodes for highly effective supercapacitors. Improved electrode capacitance, voltage window and energy density are discussed in this literature study. With a focus on the most recent electrochemical performance of both MXene and MoS2-based electrodes and devices, this review summarises recent developments in materials synthesis and its characterisation. It also helps to identify the difficulties and fresh possibilities MXenes MoS2 and its hybrid heterostructure in this developing field of energy storage. Future choices for constructing supercapacitors will benefit from this review. This review examines the newest developments in MXene/MoS2 supercapacitors, primarily focusing on compiling literature from 2017 through 2022. This review also presents an overview of the design (structures), recent developments, and challenges of the emerging electrode materials, with thoughts on how well such materials function electrochemically in supercapacitors.